Category «grass-roots» and Ukrainian music of the 19th century - Dubrovnyi, Taras (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. Actuality of theme. In a detailed analysis of samples of domestic artistic production of the mentioned period, we are convinced that the general level of musical creativity also does not always fit into the generally recognized levels of quality, going beyond the usual delineations of the categories of "high", "low" and "grassroots" art. On the one hand, it is objectively connected with socio-cultural circumstances that did not contribute to the achievement of the level of "high" samples, equivalent to the Western European culture of the time, and on the other hand, in terms of its semantic and substantive content, it does not quite correspond to the next "low" level context At the same time, the category of "grassroots" etymologically has a mostly pejorative, underestimation of artistic creativity as undeveloped and, accordingly, carries negative semantics. The main objective of the study due to the expansion of the terminological compendium, adjust the established assessments of musical works, objectifying them as much as possible. The object of analysis for terminological clarification and categorical expansion was the composer’s works, which were based on folklore elements. The subject of the research is works intended for daily use, salon, home music-making of the 19th century. The methodology are related to the main purpose of the research and rely on the historicalgenetic, socio-cultural and national context. Results and conclusions. So, we believe that the term Grassroots proposed by us to characterize examples of musical culture at both the amateur and professional levels expands the musicological thesaurus and emphasizes the qualitative aspects of national art, the basis of which is the ethnic, folklore principle. In music, a sign of belonging to the grass-roots can be considered to rely on metrorhythmic, modal and melodic foundations, as well as on the verbal content of a folk song. Focusing, first of all, on the social and national dimensions, grass-roots can be differentiated according to the "high" and/or "grassroots" levels of culture, while observing the main principle - reliance on folklore national sources with a characteristic "bottom-up" initiative. At the same time, grass-roots art exists as a separate level between "grassroots" and "high" styles. Musical samples of grass-roots art, due to the possession of the qualities of a high style and, at the same time, due to the simplification of certain elements of musical expression, are usually aimed at a wide, democratic audience and are accessible for understanding and perception.